2013
DOI: 10.3762/bjoc.9.192
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed enantioselective desymmetrization of aziridines and epoxides

Abstract: SummaryEnantioselective desymmetrization of meso-aziridines and meso-epoxides with various nucleophiles by organocatalysis has emerged as a cutting-edge approach in recent years. This review summarizes the origin and recent developments of enantioselective desymmetrization of meso-aziridines and meso-epoxides in the presence of organocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 94 publications
(56 reference statements)
0
48
0
Order By: Relevance
“…Subsequent deoxygenation of the hydroxyl group with Et 3 SiH furnished the corresponding lactams in ees up to 99%. Early studies on the selective hydrogenation of one carbonyl 30 group in cyclic carboxylic acid anhydrides to lactones showed that ruthenium-bisphosphine complexes can efficiently catalyse this transformation. 55 This pioneering work from Lyons et al paved the way to desymmetrisations of chiral or meso anhydrides by asymmetric hydrogenation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent deoxygenation of the hydroxyl group with Et 3 SiH furnished the corresponding lactams in ees up to 99%. Early studies on the selective hydrogenation of one carbonyl 30 group in cyclic carboxylic acid anhydrides to lactones showed that ruthenium-bisphosphine complexes can efficiently catalyse this transformation. 55 This pioneering work from Lyons et al paved the way to desymmetrisations of chiral or meso anhydrides by asymmetric hydrogenation.…”
Section: Methodsmentioning
confidence: 99%
“…This chemistry has already been comprehensively reviewed elsewhere, 64 and therefore, is not discussed here. Nonetheless, some influential examples of biocatalytic desymmetrisations of 30 compounds with pro-stereogenic carbons (cyclopentane-1,3diones 60, 65 cyclohexane-1,3-diones 62, 66 bicyclic diketones 64, 67 and acyclic diketones 66 68 The outstanding method from Yamada and co-workers in desymmetrising acyclic 1,3-diketones by catalytic borohydride reduction in the presence of a chiral -ketoiminato cobalt(II) 45 catalyst furnished the corresponding aldol-type compounds 72 with high diastereoselectivity (de > 98% in favour of the anti diastereoisomer) and enantioselectivity (up to 99% ee; see Scheme 6 (a)). Yamada's method 69 is an interesting alternative to aldol-chemistry for the preparation of highly enantioenriched hydroxyketones, with the inherent attractiveness that the stereoselective preparation of enolates is not required.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The epoxidation of a carbon-carbon double bond and the ring opening of resulting oxiranes with a wide range of nucleophiles is a common method to introduce various functional groups onto the skeleton of a certain organic scaffold [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%